Aplicación de la metodología de las 5s para mejorar la productividad de huevos en la empresa Avícola Mishell ubicada en el cantón Saquisilí provincia de Cotopaxi. - Cirino Chanatasig, Santiago Agustin (2023)
The present investigation has as a general objective to apply the "5S" methodology, through the identification of processes, for the continuous improvement of the poultry company "Mishell". At present, competitiveness, optimization of resources, demand for efficient and quality businesses, are some of the essential factors for organizations to seek recognition and prestige at a local and national level, which is why it is necessary and essential to seek continuous process improvements. The results obtained allowed us to identify the operational problems for each stage of the process since the company is at a 2S level, which means that it needs greater control in the collection of eggs, as well as low productivity due to the lack of basic knowledge of the 5S methodology.